A new species of the wolf spider genus Arctosa (Araneae, Lycosidae) from Southern Brazil - Cruz da Silva, Estevam Luís (2008)
A new species of the wolf spider genus Arctosa C. L. Koch, 1847 is described and illustrated, based on material collected in Sapiranga, Southern Brazil. Members of Arctosa are known to build burrows in sandy lake shores, but this new species is found under the rocks on the margins of small streams. Females with eggsacs and males can be found all year, being more abundant in the summer period.